2001
DOI: 10.2135/cropsci2001.1779
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and End‐Use Qualities of Wheat streak mosaic virus Resistant Spring Wheat

Abstract: The WSMV-resistant germplasm, KS93WGRC27, contains a translocation from Thinopyrum intermedium Development of wheat (Triticum aestivum L.) cultivars resistant (Host) Barkworth and Dewey chromosomal arm 4J s to Wheat streak mosaic virus (WSMV) that remain productive in the absence of the disease would benefit wheat growers. A wheat that carries the resistance gene Wsm1 (Lay et al., 1971; germplasm (KS93WGRC27) carrying a Thinopyrum intermedium Friebe et al., 1991; Gill et al., 1995; Chen et al., 1998). (Host) B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…Test weights were significantly greater in resistant lines, both across and within all populations. Baley et al (2001) observed a similar effect in spring wheats.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Test weights were significantly greater in resistant lines, both across and within all populations. Baley et al (2001) observed a similar effect in spring wheats.…”
Section: Resultsmentioning
confidence: 58%
“…Previous research on the agronomic and quality effects of Wsm1 has been conducted using spring wheats (Baley et al, 2001;Sharp et al, 2002) in the Northwestern United States. Baley et al (2001) compared the agronomic performance of resistant to susceptible lines of spring wheat populations under both inoculated and non-inoculated conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wsm2 was eff ective against WSMV at 18°C but ineffective at 24°C (Seifers et al, 2006). Signifi cant environmental eff ects that resulted in inconsistency and unpredictability of the consequences of WSMV infection have been observed in fi eld experiments (Baley et al, 2001;Thomas et al, 2004). Therefore, when comparing resistance to WSMV in wheat cultivars based on observation of disease incidence and severity or studying inheritance of resistance in a population, it is important to minimize environmental eff ects, especially temperature variation, that could potentially confound the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, Wsm1 is the only named gene conferring resistance to WSMV (Friebe et al, 1991) and being used in cultivar improvement (Baley et al, 2001; Sharp et al, 2002; Divis et al, 2006). Wsm1 was transferred from Th.…”
mentioning
confidence: 99%